No Association of Variants of the NPY-System With Obsessive-Compulsive Disorder in Children and Adolescents - Franke, Maximilian; Conzelmann, Annette; Grünblatt, Edna; Werling, Anna M.; Spieles, Helen; Wewetzer, Christoph; Warnke, Andreas; Romanos, Marcel; Walitza, Susanne; Renner, Tobias J. (Frontiers in Molecular Neuroscience, 2019)
Obsessive compulsive disorder (OCD) causes severe distress and is therefore counted by the WHO as one of the ten most impairing illnesses. There is evidence for a strong genetic under-pinning especially in early onset OCD. Though several genes involved in neurotransmission have been reported as candidates there is still need to identify new pathways. In this study, we focussed on genetic variants of the Neuropetide Y (NPY) system. NPY is one of the most abundant neuropeptides in the human brain with emerging evidence of capacity to modulate stress response, which is of high relevance in OCD. We focussed on tag-SNPs of NPY and its receptor gene NPY1R in a family-based approach. The sample comprised 86 patients (children and adolescents) with early onset OCD with both their biological parents. However, this first study on genetic variants of the NPY-system could not confirm association between the investi-gated SNPs and early onset OCD.